2022
DOI: 10.3390/ma15010325
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Lightweight Ceramsite from Solid Waste Using SiC as a Foaming Agent

Abstract: SiC was chosen as the foaming agent, and river bottom silt, waste oil sludge, paint bucket slag, and fly ash were used as raw materials, to prepare lightweight ceramsite without adding any chemical additives. The effects of SiC dosing and sintering temperature on various properties of the ceramsite were studied, and the pore-forming mechanism of the lightweight ceramsite was clarified by thermal analysis and X-ray diffraction analysis. The results showed that the single ceramsite compressive strength, water ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The comparison of the bulk density, water absorption, and particle compressive strength of the ceramsite in this study with those reported in other literature was presented in Supplementary Table S4 (Sun et al, 2021;Pei et al, 2022;Shang et al, 2022;Jia et al, 2023;Li et al, 2023). It was worth noting that all primary raw materials utilized were industrial solid waste materials, and the produced ceramsite in this work demonstrated exceptional performance in terms of both compressive strength and density.…”
Section: Analysis Of Heavy Metals Leaching Behavior In Ceramsitesmentioning
confidence: 59%
“…The comparison of the bulk density, water absorption, and particle compressive strength of the ceramsite in this study with those reported in other literature was presented in Supplementary Table S4 (Sun et al, 2021;Pei et al, 2022;Shang et al, 2022;Jia et al, 2023;Li et al, 2023). It was worth noting that all primary raw materials utilized were industrial solid waste materials, and the produced ceramsite in this work demonstrated exceptional performance in terms of both compressive strength and density.…”
Section: Analysis Of Heavy Metals Leaching Behavior In Ceramsitesmentioning
confidence: 59%
“…In the raw material, 1 wt% of SiC was used as a foaming agent. Therefore, the following reaction would occur during the roasting stage [30]: The finished FMC was obtained by cooling the granules to room temperature, and its basic performance was measured.…”
Section: Preparation Methods Of the Fmcmentioning
confidence: 99%
“…A modified method was utilized to produce ceramsite, which is a lightweight ceramic ball using Akadama clay (Shang et al 2022). The clay has a pH of 6.9, an electroconductivity (EC) of 0.052 ms/cm, and a water absorption rate of 20%.…”
Section: Ceramsite Preparationmentioning
confidence: 99%